Ethics of trending in pharmaceutical & therapeutic-related biotechnology - M. Gameil, Abeir Hussein; Kabbashi, Nassereldeen Ahmed (2013)
There exist a large disparity between the developed and developing countries, in terms of accessing affordable medication. Pharmaceuticals are generally costly; due to the high capital costs involved, as well as the cost of abiding by regulations, standardization, safety & purity concerns. However, it can also be observed that the biotechnology industry has shifted focus towards health areas that would bring the most profits. This may seem alright when the health areas are those related to diseases that rank high in mortality. However, what of health areas that do not put the patients in mortal danger, for example, skin diseases, weight-loss, and hair loss? Compared to cancer, diabetes, asthma, and kidney failure, obviously these issues, whilst being damaging to self-esteem & social life, are not as severe. On the other hand, there are children who have rare and debilitating diseases that limit their life expectancy to childhood. If the industries as well as the research funders continue to trend this way, what would remain of funds for these diseases? This paper seeks to enlighten on the underlying ethical dangers of this trend. The paper also re-emphasizes the value of technology transfer in aiding research related to these diseases for purposes of early diagnosis as well as therapeutics, through biotechnology.